Ultrasensitive detection by maxillary palp neurons allows non-host recognition without consumption of harmful allelochemicals. (July 2021) - Shii, Fumika; Mang, Dingze; Kasubuchi, Mayu; Tsuneto, Kana; Toyama, Tomoko; Endo, Haruka; Sasaki, Ken; Sato, Ryoichi
Graphical abstract: Highlights: B. mori larvae recognize non-host plant by sensing leaf-surface secondary compounds. B. mori larvae recognize non-host plant without eating by using maxillary palps. Neurons in the maxillary palp respond to a leaf-surface extract of non-host cherry. Neurons in the maxillary palp respond to attomolar coumarin solution. The taste receptor BmGr53 respond to a leaf-surface extract of non-host cherry. Abstract: Most lepidopteran insect larvae exhibit stepwise feeding behaviors, such as palpation using the maxillary palps (MPs) followed by test biting and persistent biting. However, the purpose of palpation has been unclear. In particular, nothing is known about the neurons in the MP and their mode of recognition of undesired plants, although such neurons have been suggested to exist. In this study, we used larvae of the stenophagous insect Bombyx mori and compared the roles of palpation and test biting in the selection of feeding behavior. When the larvae were given non-host plant leaves, they did not initiate test biting, indicating that non-host plant leaves were recognized via palpation without biting, and that this behavior resulted in a lack of persistent biting, as the leaves were judged non-suitable for consumption. Surface extracts of inedible leaves significantly suppressed test biting of mulberry leaves, a host plant of B. mori, suggesting that secondary metabolites on the leaf surface of inedible leaves function as test biting suppressors, even when another conditions are suitable for test biting. The allelochemical coumarin, which is found in the inedible leaves of cherry, Cerasus speciosa, significantly suppressed test biting of mulberry leaves, suggesting that coumarin is a possible deterrent to the eating of cherry leaves. Using the electrophysiological method of tip recording and a leaf-surface extract as the test material, leaf-surface compound-responsive neurons were identified in the MP. In addition, several neurons that respond to coumarin in the attomolar range were identified, suggesting that the larvae use ultrasensitive neurons in the MP to recognize inedible leaves. In the HEK293T cell heterologous expression system, the B. mori gustatory receptors BmGr53 and BmGr19, which were previously found to be expressed in the MP and to respond to coumarin in the attomolar range, responded to a leaf-surface extract of C. speciosa, suggesting that these receptors may be present on the inedible-leaf-recognizing neurons of the MP. These findings suggest that ultrasensitive plant secondary metabolite-recognizing neurons in the MP allow for the recognition of non-host plants via palpation without risking damage caused by ingesting harmful allelochemicals.